Screening of Herbs with Potential Modulation of NLRP3 Inflammasomes for Acute Liver Failure: A Study Based on the Herb-Compound-Target Network and the ssGSEA Algorithm - Ou, Haiya; Qiu, Susu; Ye, Xiaopeng; Wang, Xiaotong (Current Topics in Medicinal Chemistry, 2025)
ObjectiveNLRP3 inflammasomes are considered to be key factors in the pathogenesis of Acute Liver Failure (ALF). Some Traditional Chinese Medicines (TCMs) have shown protective and therapeutic effects against ALF by inhibiting NLRP3 inflammasomes. However, the inhibitory effects of most TCMs on ALF remain to be further elucidated. This study aimed to screen potential herbs that can treat ALF based on the inhibition of NLRP3 inflammasomes.MethodsInitially, we constructed the target set for 502 herbs. Subsequently, based on the target set and the gene set related to the NLRP3 inflammasome, using the ssGSEA algorithm, we evaluated herb scores and NLRP3 scores in the ALF expression matrix and performed a preliminary herb screening based on score correlations. Through bioinformatics approaches, we identified the key targets for candidate herbs and determined core herbs based on the herb-compound-target network. Furthermore, molecular docking and molecular biology methods validated the screening results of the herbs.ResultsA total of 18 crucial targets associated with the inhibition of the NLRP3 inflammasome were identified, which included ALDH2, HMOX1, and VEGFA. Subsequently, based on these key targets, a set of 10 primary herbs was chosen, notably Qinghao, Duzhong, and Gouteng. Moreover, the results were verified through molecular docking and molecular dynamic simulation.ConclusionTen key herbs have been identified as potential inhibitors of the NLRP3 inflammasome, offering insights into ALF therapy for drug development.
Keywords: Single sample gene set enrichment analysis (ssGSEA)